Voice production mechanisms following phonosurgical treatment of early glottic cancer. - Mehta DD; Deliyski DD; Zeitels SM; Quatieri TF; Hillman RE (Annals of Otology, Rhinology & Laryngology, 2010)
Objectives: Although near-normal conversational voices can be achieved with the phonosurgicai management of early glottic cancer, there are still acoustic and aerodynamic deficits in vocal function that must be better understood to help further optimize phonosurgical interventions. Stroboscopic assessment is inadequate for this purpose. Methods: A newly developed color high-speed videoendoscopy (HSV) system that included time-synchronized recordings of the acoustic signal was used to perform a detailed examination of voice production mechanisms in 14 subjects. Digital image processing techniques were used to quantify glottal phonatory function and lo delineate relationships between vocal fold vibratory properties and acoustic perturbation measures. Results: The results for multiple measurements of vibratory asymmetry showed that 31% to 62% of subjects displayed higher-than-normal average values, whereas the mean values for glottal closure duration (open quotient) and periodicity of vibration fell within normal limits. The average HSV-based measures did not correlate significantly with the acoustic perturbation measures, but moderate correlations were exhibited between the acoustic measures and the SDs of the HSV-based parameters. Conclusions: The use of simultaneous, time-synchronized HSV and acoustic recordings can provide new insights into postoperative voice production mechanisms that cannot be obtained with stroboscopic assessment.